FOOTBALL COMPETITIONS ORGANIZATION - T.Q.Soitpolotov (Journal of new century innovations, 2023)
Football competitions are the main part of educational activities. They are in training increases interest, helps mass development of football in the country. Football player in games regularly not participating standing up high to the results reach can't. Competitions competition attend the level of physical, technical, tactical and moral-will training of the players and the team as a whole determines training process status and determine direction enable will give. Competition results educational work finish tool being serves.